A modified Mediterranean dietary intervention for adults with major depression: Dietary protocol and feasibility data from the SMILES trial. (9th August 2018) - Opie, Rachelle S.; O'Neil, Adrienne; Jacka, Felice N.; Pizzinga, Josephine; Itsiopoulos, Catherine
Abstract : Background: The SMILES trial was the first randomized controlled trial (RCT) explicitly designed to evaluate a dietary intervention, conducted by qualified dietitians, for reducing depressive symptomatology in adults with clinical depression. Objectives: Here we detail the development of the prescribed diet (modified Mediterranean diet (Mod i MedDiet)) for individuals with major depressive disorders (MDDs) that was designed specifically for the SMILES trial. We also present data demonstrating the extent to which this intervention achieved improvements in diet quality. Methods: The Mod i MedDiet was designed using a combination of existing dietary guidelines and scientific evidence from the emerging field of nutritional psychiatric epidemiology. Sixty-seven community dwelling individuals (Melbourne, Australia) aged 18 years or over, with current poor quality diets, and MDDs were enrolled into the SMILES trial. A retention rate of 93.9 and 73.5% was observed for the dietary intervention and social support control group, respectively. The dietary intervention (Mod i MedDiet) consisted of seven individual nutrition counselling sessions delivered by a qualified dietitian. The control condition comprised a social support protocol matched to the same visit schedule and length. Results: This manuscript details the first prescriptive individualized dietary intervention delivered by dietitians for adults with major depression. Significant improvements in dietary quality were observed among individuals randomized to the Mod i MedDiet group. These dietary improvements were also found to be associated with changes in depressive symptoms. Discussion/Conclusion: The Mod i MedDiet, a novel and individually tailored intervention designed specifically for adults with major depression, can be effectively implemented in clinical practice to manage this highly prevalent and debilitating condition. Trial registration: Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12612000251820. Registered 29 February 2012